Evaluation of a manufacturing task support system using the Task Technology Fit Model - Tjahjono, Benny; Fakun, D.; Greenough, Richard M.; Kay, John M. (Production and Operations Management Society, 2001)
This paper presents an exploratory study of a Task Support System (TSS) supporting manufacturing task operations. The study investigated the degree to which a TSS, in use in a company, actually supports the task of the shop floor personnel. The approach has been to adopt the Task-Technology Fit (TTF) instrument to measure the degree of fitness between the TSS and the associated task. The analysis gives an indication of the state of the TSS and the potential improvements that can be made. The study also shows that the instrument can be used as a foundation for the development of a hypermedia TSS and a benchmarking tool for a TSS.